HUBUNGAN TINGKAT PENGETAHUAN TENTANG IMUNISASI POLIO DENGAN TINDAKAN MENGIMUNISASI POLIO DI POSYANDU ANGGREK DESA LANGENHARJO KELURAHAN LANGENHARJO KECAMATAN GROGOL KABUPATEN SUKOHARJO - Sri Aminingsih; Diyono Diyono; Pungky Nata Yolanda (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2014)
AbstractThe background of this study is that mothers in Anggrek posyandu not know exactly what it is polio symptoms and signs, so researchers wanted to know the mother's level of knowledge about polio immunization with polio immunization completeness action in posyandu Anggrek. The purpose of the study to determine the relationship of the level of knowledge about polio immunization with polio immunizing action in posyandu Anggrek, Langenharjo Village, Village Langenharjo, Grogol, Sukoharjo, 2014. The design of this study using desan research and cross correlation secsional. The subjects were mothers with infants aged at least 11 months in posyandu Anggrek as many as 33 people. The results of the study of data obtained by distributing questionnaires and observation. The data have been collected and analyzed by chi square test with p = 0.05 p equal to 0.006 thus obtained p value <0.05 which means Ha accepted. Conclusion The results of the study indicate that there is a relationship between the level of knowledge about polio immunization with polio immunizing action in posyandu Anggrek Langenharjo Village, Village Langenharjo, Grogol, Sukoharjo, 2014.Keywords: Polio Immunization Knowledge, Action Immunising Polio